Exploring Maxim of Cooperative Principle in The Wild Robot Movie: A Pragmatic Approach - Nurjannah Nurjannah; Sahur Saerudin (CV Projurnal Mitra Publikasi, 2025)
This study aims to assess the concept of cooperation by analyzing the dialogue among characters in the Wild Robot movie. Since words, phrases, and sentences would be utilized to explain the data, a descriptive qualitative method was employed for analysis. The quantitative approach yields descriptive data, specifically in the form of phrases or words that succinctly explain the findings of the conducted research. The data consists of conversational fragments that obey cooperative principle's maxim. The source of data is derived from the dialogue of the characters in the film About Time. The researcher employed non-participatory note-taking techniques and the observational approach to get the data. The outcomes of the analysis of the cooperative principle performed by the characters in the movie is described in this study using a qualitative methodology. To analyze the data, the pragmatic identity technique was utilized. The results demonstrated that the dialogue in the film About Time contained all four of the cooperation principle's maxim. The investigator discovered 19 maxims. According to the results, there were 2 (11%) data maxim of manner, 5 (26%) data maxims of quality, 7 (37%) data maxims of relation, and 5 (26%) data maxims of quantity. In conclusion, the maxim of the maxim of relation included the most data. The maxim of manner had the least amount of data.